Analysis of the Influence of Interest Rates, Inflation, Rupiah Exchange Rates, World Oil Prices, And World Gold Prices on JCI (Case Study on JCI on the IDX during the Period January 2015 – December 2024) - Harmono Sri Waluyo (Jurnal Indonesia Sosial Sains, 2025)
Indonesian Stock Exchange Composite Index (JCI) is significantly influenced by macroeconomic and commodity factors, yet prior studies show inconsistent findings regarding their impacts, especially in the post-pandemic context. This study aims to clarify the effects of Interest Rates, Inflation, Rupiah Exchange Rates, World Oil Prices, and World Gold Prices on the JCI from 2015 to 2024. Employing a quantitative approach through explanatory research, we analyzed 120 time-series samples using multiple linear regression analysis. The results reveal that World Oil Prices have a significant positive effect on the JCI (β = 0.358), while World Gold Prices also show a positive correlation (β = -0.146). In contrast, Interest Rates, Inflation, and Exchange Rates do not exhibit significant impacts on the index. The pronounced influence of oil prices highlights the sensitivity of Indonesia’s market to commodity fluctuations. Policymakers and investors are advised to focus on oil price volatility and geopolitical risks, while also diversifying their portfolios to address uncertainties related to gold prices. Future research should investigate sectoral asymmetries and incorporate high-frequency data to provide deeper insights into these dynamics.